Performance curve in domestic gas meter calibration system - Mohsin, Rahmat; Ramly @ Hassan, Noor Shafine; Abd. Majid, Zulkifli (Penerbit UTM Press, 2008)
This project is focused on the performance curve of gas metering calibration system for low pressure low flow rate domestic gas meter. Visual Basic 6.0 has been employed to carry out comparison of the calibration performance curve. Data gathered from previous work will be used to enable performance comparison. Wet type gas meter will be used as the reference meter in order to calibrate domestic gas meter due to its high accuracy and suitable operating condition at low pressure and low flow rate. Diaphragm gas meter has been selected as predominant domestic gas meter that normally represents common domestic gas meter application as a gas-measuring device. From the experiment, several operating condition will be carried out to obtain high accuracy measurement to calibrate the diaphragm meter with flow capacity up to 1.20 m3/hr at an operating pressure of 35 milibar (14 inches water column), with setting temperature of 19 Â°C to 23 Â°C. The operation of calibration process incorporates the use of three types of test fluid namely; compressed air, nitrogen and liquefied petroleum gas. Results obtained show that pressure drop increases when flow rate increases and error of new meters increases with the increasing of flow rate until a maximum point reached at less than 2.0%. Therefore all the results obtained are valid and traceable.